Kidney Retransplantation after Graft Failure: Variables Influencing Long-Term Survival - Jonas Ehrsam; Fabian Rössler; Karoline Horisberger; Kerstin Hübel; Jakob Nilsson; Olivier de Rougemont (Journal of Transplantation)
Background. There is an increasing demand for kidney retransplantation. Most studies report inferior outcomes compared to primary transplantation, consequently feeding an ethical dilemma in the context of chronic organ shortage. Objective. To assess variables influencing long-term graft survival after kidney retransplantation. Material and Methods. All patients transplanted at our center between 2000 and 2016 were analyzed retrospectively. Survival was estimated with the Kaplan–Meier method, and risk factors were identified using multiple Cox regression. Results. We performed 1,376 primary kidney transplantations and 222 retransplantations. The rate of retransplantation was 67.8% after the first graft loss, with a comparable 10-year graft survival compared to primary transplantation (67% vs. 64%, p=0.104) but an inferior graft survival thereafter (log-rank p=0.026). Independent risk factors for graft survival in retransplantation were age ≥ 50 years, time on dialysis ≥1 year, previous graft survival <2 years, ≥1 mild comorbidity in the Charlson–Deyo index, active smoking, and life-threatening complications (Clavien–Dindo grade IV) at first transplantation. Conclusion. Graft survival is comparable for first and second kidney transplantation within the first 10 years. Risk factors for poor outcomes after retransplantation are previous graft survival, dialysis time after graft failure, recipient age, comorbidities, and smoking. Patients with transplant failure should have access to retransplantation as early as possible.